The Role of Peer Learning in Enhancing Student Engagement - Imran Shahid (Global Journal of Multidisciplinary and Applied Sciences, 2023)
Peer learning is an instructional strategy in which students engage with and learn from each other, enhancing their understanding of the material and improving their academic outcomes. This paper explores the role of peer learning in fostering student engagement, focusing on how collaborative learning environments promote active participation, critical thinking, and deeper understanding. It discusses various peer learning models, including peer tutoring, study groups, and collaborative projects, and examines the benefits of peer learning in developing communication skills, boosting confidence, and creating a sense of community. The study also addresses the challenges associated with peer learning, such as uneven participation and the need for effective facilitation. The paper concludes with recommendations for educators on how to successfully implement peer learning strategies to maximize student engagement and enhance learning outcomes.